Plan de negocios para la apertura de un centro médico de rehabilitación y terapia física en el distrito de Jesús María - Barron Lopez, Ricardo (2020)
The objective of this project is determining of viability to open a medical rehabilitation and physical therapy center in Jesús María district. To corroborate whether the center is viable, the project focuses on analyzing the possible profitability to obtain taking into account various factors.The project is divided into ten chapters, the first chapter being the general aspects. Among the aspects are the objectives to be achieved with the research, characteristics of the sector in the meeting of the project and the analysis of the Peruvian economic environment.In the subsequent two chapters, it identifies the legal and tax aspects to which the project is based and defines the organizational design that will take the form according to the identification of the type of service and its characteristics. In addition, it analyzes the methodological aspects through various techniques.In chapter four the market study is carried out, a commercial study, where the target market from which the project starts quantitatively is identified. Subsequently, the demand and supply in the market is evaluated, referring to the study topic.In the next four chapters, define the marketing plan to work to achieve established sales for unmet demand, the servuction and quality processes according toeconomic scope, the location analysis of the center and the human resources processes necessary to maintain personnel. satisfied and with a high level of attention.In chapter nine the strategic planning of the project is carried out, establishing the competitive profile, the policies, the schedules and the schedule starting from the implementation of the business.In the final chapter, we carry out the financial projections with a duration of 5 years, having 2021 as the effective start year. Analyze various indicators to know the profitability level of the project.